Current collector, application thereof, secondary battery, battery module, battery pack and electric device
Patent Information
- Application Number
- CN202280096217.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2024-12-27
AI Technical Summary
The current collector in the existing secondary battery has uneven local current density, which leads to the formation of dendrites, which poses safety risks and cannot meet the application needs of the new generation of electrochemical systems.
A current collector with an undercoat formed on the surface is used. The undercoat contains carbon nanomaterials, including zero-dimensional, one-dimensional and two-dimensional carbon materials. Its nanoscale structure and arrangement improve the uniformity of nucleation site distribution. Reduce the nucleation overpotential of metal ion deposition, inhibit dendrite growth, and improve the cycle performance and safety of the battery.
It effectively inhibits the dendrite growth of metal ions, reduces the DC impedance of the battery after 100 cycles, improves the Coulombic efficiency and capacity retention rate, and enhances the cycle performance and safety of the battery.
Smart Images

Figure CN119213584A_ABST
Abstract
Description
Current collector, application thereof, secondary battery, battery module, battery pack and electrical device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a current collector, applications thereof, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] The current collector, an integral component of a secondary battery structure, plays a crucial role in carrying active materials, providing a current path, and connecting internal and external circuits. Existing current collectors, primarily made of metal, are prone to localized uneven current density, leading to the formation of dendrites on their surfaces, posing safety risks and failing to meet the application needs of next-generation electrochemical systems.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a current collector with a primer layer formed on the surface, which is conducive to the uniform deposition of metal ions on the surface of the current collector and improves the cycle performance and safety of the battery.
[0006] In a first aspect of the present application, a current collector having a base coating formed on its surface is provided, wherein the base coating comprises a carbon nanomaterial, and the carbon nanomaterial comprises at least two selected from zero-dimensional carbon materials, one-dimensional carbon materials and two-dimensional carbon materials.
[0007] Carbon nanomaterials induce the deposition of metal ions on the surface of the basecoat layer through adsorption. Their nanoscale structure and arrangement improve the uniformity of the distribution of nucleation sites, which is conducive to the uniform deposition of metal ions. At the same time, the combination of three different sizes of carbon materials, zero-dimensional carbon materials, one-dimensional carbon materials and two-dimensional carbon materials, has a synergistic effect to form a "point-line-surface" network structure, giving full play to their respective advantages to achieve multi-level filling and connection effects, further improving the uniformity of the distribution of nucleation sites, and reducing the nucleation overpotential of metal ion deposition. It can effectively induce the uniform deposition of metal ions and regulate the metal ion deposition behavior, so that the dendrite growth of metal ions is effectively suppressed. In addition, the basecoat layer containing carbon nanomaterials is also beneficial to reduce the DC impedance of the battery after 100 cycles, improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0008] In any embodiment, the carbon nanomaterial in the undercoat layer includes the zero-dimensional carbon material and the one-dimensional carbon material.
[0009] The inventors creatively discovered that the combination of zero-dimensional carbon materials and one-dimensional carbon materials is more conducive to reducing the surface density of the base coating and the nucleation overpotential of metal ions, further inducing the uniform deposition of metal ions on the current collector, and greatly improving the capacity retention rate of the battery after 100 cycles.
[0010] In any embodiment, the zero-dimensional carbon material has a median particle size Dv50 of 10 nm to 60 nm.
[0011] Controlling the median particle size Dv50 of zero-dimensional carbon materials to 10nm~60nm can further improve the uniformity of the carbon nanomaterial arrangement, greatly reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0012] In any embodiment, the aspect ratio of the one-dimensional carbon material is 500 to 50,000, and can be optionally 1,000 to 10,000.
[0013] Controlling the aspect ratio of the one-dimensional carbon material to 500-50,000 effectively reduces the nucleation overpotential of metal ion deposition, inhibits dendrite growth, reduces the DC impedance of the battery after 100 cycles, and improves the battery's coulombic efficiency and capacity retention after 100 cycles. Controlling the aspect ratio of the one-dimensional carbon material to 1,000-10,000 can further improve the capacity retention after 100 cycles.
[0014] In any embodiment, the one-dimensional carbon material has a tube diameter of 1 nm to 20 nm, optionally 5 nm to 20 nm, and a length of 10 μm to 50 μm, optionally 20 μm to 30 μm.
[0015] Controlling the tube diameter of the one-dimensional carbon material to 1nm-20nm and the length to 10μm-50μm can effectively reduce the nucleation overpotential of metal ion deposition, inhibit dendrite growth, reduce the DC impedance of the battery after 100 cycles, and improve the battery's Coulombic efficiency and capacity retention after 100 cycles. Controlling the tube diameter of the one-dimensional carbon material to 5nm-20nm can further leverage the advantages of the one-dimensional carbon material, further reducing the nucleation overpotential of metal ion deposition and the DC impedance of the battery after 100 cycles, and improving the battery's Coulombic efficiency and capacity retention after 100 cycles. Controlling the length of the one-dimensional carbon material to 20μm-30μm can further reduce the DC impedance of the battery after 100 cycles.
[0016] In any embodiment, the median particle size Dv50 of the two-dimensional carbon material is not greater than 500 nm.
[0017] Controlling the median particle size Dv50 of the two-dimensional carbon material to no more than 500nm can effectively reduce the nucleation overpotential of metal ions, inhibit the growth of dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0018] In any embodiment, the mass ratio of the two-dimensional carbon material, the one-dimensional carbon material, and the zero-dimensional carbon material is (0-10):(0-9):(0-9.5), wherein the masses of at least two of the two-dimensional material, the one-dimensional carbon material, and the zero-dimensional carbon material cannot be 0 at the same time.
[0019] Controlling the mass ratio of two-dimensional carbon materials, one-dimensional carbon materials, and zero-dimensional carbon materials within an appropriate range can effectively reduce the nucleation overpotential of metal ions, inhibit the growth of dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0020] In any embodiment, the mass ratio of the one-dimensional carbon material to the zero-dimensional carbon material is (2:8) to (7:3).
[0021] Controlling the mass ratio of one-dimensional carbon material and zero-dimensional carbon material within an appropriate range can greatly reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0022] In any embodiment, the zero-dimensional carbon material comprises at least one selected from conductive carbon black, carbon nanodots, and fullerenes, and the conductive carbon black comprises at least one selected from Super P, Ketjen black, and acetylene black.
[0023] The above-mentioned zero-dimensional carbon material has excellent conductivity, which allows the base layer to serve as a conductive network for rapid electron transmission. Its nanoscale structure and arrangement also help to reduce the current density, thereby reducing the overpotential of metal ion deposition, promoting the uniform deposition of metal ions, and inhibiting the dendritic behavior of metal ions. At the same time, the above-mentioned zero-dimensional carbon material also helps to reduce the DC impedance of the battery after 100 cycles, improve the battery's coulombic efficiency and capacity retention rate after 100 cycles.
[0024] In any embodiment, the one-dimensional carbon material comprises at least one selected from carbon nanotubes, carbon nanohorns, carbon nanofibers, and carbon nanorods, and the carbon nanotubes comprise at least one selected from single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0025] The one-dimensional carbon material has excellent electrical conductivity, allowing the undercoat layer to serve as a conductive network for rapid electron transport. Its nanoscale structure and arrangement also help reduce current density, thereby lowering the overpotential for metal ion deposition, promoting uniform deposition of metal ions, and inhibiting dendritic behavior. Furthermore, the one-dimensional carbon material also helps reduce the DC impedance of the battery after 100 cycles, improving the battery's coulombic efficiency and capacity retention after 100 cycles.
[0026] In any embodiment, the two-dimensional carbon material comprises at least one selected from graphene and graphyne.
[0027] The two-dimensional carbon material has excellent electrical conductivity, allowing the undercoat layer to serve as a conductive network for rapid electron transport. Its nanoscale structure and arrangement also help reduce current density, thereby lowering the overpotential for metal ion deposition, promoting uniform deposition of metal ions, and inhibiting dendritic behavior. Furthermore, the two-dimensional carbon material also helps reduce the DC impedance of the battery after 100 cycles, improving the battery's coulombic efficiency and capacity retention after 100 cycles.
[0028] In any embodiment, the one-dimensional carbon material in the primer layer is single-walled carbon nanotubes, and the zero-dimensional carbon material in the primer layer is conductive carbon black.
[0029] The one-dimensional carbon material in the base coating is single-walled carbon nanotubes, and the zero-dimensional carbon material in the base coating is conductive carbon black, which can further reduce the overpotential of metal ion deposition, thereby reducing the DC impedance of the battery after 100 cycles to a greater extent, and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0030] In any embodiment, the thickness of the primer layer is 0.5 μm to 15 μm, and optionally 1 μm to 8 μm.
[0031] Controlling the thickness of the primer layer to 0.5μm to 15μm can provide sufficient nucleation sites to facilitate uniform deposition of metal ions, effectively reducing the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, improving the battery's coulombic efficiency and capacity retention after 100 cycles, and also avoiding the impact of the primer layer on energy density. Controlling the thickness of the primer layer to 1μm to 8μm can further reduce the nucleation overpotential of metal ions, giving greater balance between nucleation sites and energy density.
[0032] In any embodiment, the surface density of the primer layer is 0.5 mg / 1540.25 mm 2 ~50mg / 1540.25mm 2 , optional 1mg / 1540.25mm 2~25mg / 1540.25mm 2 .
[0033] Control the surface density of the primer layer to 0.5mg / 1540.25mm 2 ~50mg / 1540.25mm 2 , which is conducive to the uniform distribution of nucleation sites and promotes the uniform deposition of metals without affecting the transmission behavior of electrons; the surface density of the base coating is controlled to be 1mg / 1540.25mm 2 ~25mg / 1540.25mm 2 , further taking into account both nucleation sites and electron transport.
[0034] In any embodiment, the primer layer further comprises a binder, and the mass ratio of the carbon nanomaterial to the binder in the primer layer is 1:(0.1-2), and can be optionally 1:(0.1-1).
[0035] Controlling the mass ratio of carbon nanomaterial to binder in the primer layer to 1:(0.1-2) can effectively reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the battery's coulombic efficiency and capacity retention after 100 cycles. Controlling the mass ratio of carbon nanomaterial to binder in the primer layer to 1:(0.1-1) can further reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the battery's coulombic efficiency and capacity retention after 100 cycles.
[0036] In any embodiment, the current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector, and a composite current collector.
[0037] The above-mentioned current collector has excellent tensile strength and ductility, which is beneficial to the stability and safety of the battery.
[0038] In a second aspect of the present application, a use of a current collector in any embodiment in a sodium battery is provided.
[0039] A third aspect of the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a current collector in any embodiment.
[0040] The secondary battery has excellent cycle performance.
[0041] In any embodiment, the secondary battery includes at least one of a lithium battery, a sodium battery, a magnesium battery, a potassium battery, and a zinc battery.
[0042] In any embodiment, the secondary battery is a negative electrode-free sodium battery. The negative electrode-free sodium battery can have a high energy density.
[0043] A fourth aspect of the present application provides a battery module including the secondary battery according to the third aspect of the present application.
[0044] A fifth aspect of the present application provides a battery pack, comprising the secondary battery of the third aspect of the present application or the battery module of the fourth aspect of the present application.
[0045] A sixth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, and the battery pack of the fifth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0047] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0048] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0049] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0050] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0051] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0052] Description of reference numerals:
[0053] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0054] Below, the embodiments of the current collector and its application, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0055] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0058] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0059] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0060] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0061] Metal secondary batteries are secondary batteries that use metal materials (such as lithium, sodium, magnesium, potassium, and other metals) as their negative electrodes. The metal material on the negative electrode current collector can be pre-deposited on the current collector surface as the negative electrode active material, or it can be deposited in situ on the current collector surface during the charge and discharge process. This means that metal secondary batteries include sodium batteries, lithium batteries, magnesium batteries, potassium batteries, and batteries without negative electrodes. The negative electrode sheet in a battery without negative electrodes uses a negative electrode current collector and does not contain negative electrode active material. During the initial charge and discharge process, metal ions are deposited in situ on the negative electrode current collector.
[0062] Metal batteries currently face numerous challenges. For example, in sodium batteries without negative electrodes, during charge and discharge, sodium undergoes uneven deposition and precipitation on the current collector surface, forming sodium dendrites. Some dendrites break off, resulting in "dead sodium or lithium," reducing the battery's energy density and cycle performance. Other dendrites continue to grow and eventually puncture the separator, causing a short circuit and potentially leading to safety accidents.
[0063] [current collector]
[0064] Based on this, the present application proposes a current collector having a primer layer formed on its surface, wherein the primer layer comprises a carbon nanomaterial, and the carbon nanomaterial comprises at least two selected from zero-dimensional carbon materials, one-dimensional carbon materials and two-dimensional carbon materials.
[0065] In this article, the term "carbon nanomaterial" refers to a carbon material with at least one dimension in the three-dimensional space being in the nanometer size (1nm to 100nm) or composed of them as basic units, which is roughly equivalent to the scale of 10 to 1000 atoms closely packed together.
[0066] As used herein, the term "zero-dimensional carbon material" refers to a carbon material having a size of 100 nm or less in all three dimensions. Examples of zero-dimensional carbon materials include, but are not limited to, one or more of Super P, Ketjen black, acetylene black, carbon nanodots, and fullerenes.
[0067] As used herein, the term "one-dimensional carbon material" refers to a carbon material having two dimensions less than or equal to 100 nm. A one-dimensional carbon material can be considered a line. Examples of one-dimensional carbon materials include, but are not limited to, one or more of carbon nanotubes, carbon nanohorns, carbon nanofibers, and carbon nanorods.
[0068] As used herein, the term "two-dimensional carbon material" refers to a carbon material having a size of 100 nm or less in one dimension, and the two-dimensional carbon material can be considered as a plane. By way of example, the two-dimensional carbon material includes but is not limited to graphene and / or graphyne.
[0069] As used herein, the term "Super P" refers to carbon black particles that aggregate to form grape-shaped shapes.
[0070] As used herein, the term "Ketjen black" refers to carbon black having branched chains.
[0071] As used herein, the term "acetylene black" refers to carbon black particles that aggregate to form chains.
[0072] In this article, the term "carbon nanodots" refers to zero-dimensional carbon nanomaterials composed of spherical carbon particles.
[0073] As used herein, the term "fullerene" refers to a hollow molecule composed of carbon with a unique zero-dimensional structure.
[0074] In some embodiments, the undercoat layer comprises a zero-dimensional carbon material and a one-dimensional carbon material. In some implementations, the undercoat layer comprises a zero-dimensional carbon material and a two-dimensional carbon material. In some implementations, the undercoat layer comprises a one-dimensional carbon material and a two-dimensional carbon material. In some implementations, the undercoat layer comprises a zero-dimensional carbon material, a one-dimensional carbon material, and a two-dimensional carbon material.
[0075] Carbon nanomaterials induce metal ion deposition on the surface of the undercoat layer through adsorption. Their nanoscale structure and arrangement improve the uniformity of nucleation site distribution, facilitating uniform metal ion deposition. Furthermore, the combination of three different carbon materials—zero-dimensional, one-dimensional, and two-dimensional—works synergistically to form a "point-line-surface" network structure. The zero-dimensional carbon material fills the gaps, the one-dimensional carbon material uses its length advantage to bridge the gaps, and the two-dimensional carbon material uses its large specific surface area to increase current collector coverage. This further improves the uniform dispersion of the carbon nanomaterials, mitigates excessive local current density variations, and reduces the degree of direct contact between the current collector and the deposited metal ions. The three different carbon nanomaterial sizes leverage their respective advantages to achieve multi-level filling and connection effects, further improving the uniformity of nucleation site distribution and reducing the nucleation overpotential for metal ion deposition. This effectively induces uniform metal ion deposition and regulates metal ion deposition behavior, effectively suppressing metal ion dendrite growth. In addition, the bottom coating layer containing carbon nanomaterials is also beneficial to reducing the DC impedance of the battery after 100 cycles, improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0076] As used herein, the term "nucleation site" refers to a location where metal ions are deposited by obtaining electrons at the negative electrode to form metal atoms.
[0077] In this article, the term "nucleation overpotential" refers to the potential required for metal ions to obtain electrons at the negative electrode to form metal atoms for deposition.
[0078] In this paper, the term “dendrite” refers to the non-uniform deposition of metal ions leading to the non-ideal growth of localized areas of the metallic phase.
[0079] In this article, the nucleation overpotential is mainly used to characterize the potential required for metal ion deposition, which can reflect the uniformity of metal ion deposition and can be tested by any known method.
[0080] In this article, coulombic efficiency refers to the first coulombic efficiency, which is mainly used to characterize the ratio of battery discharge capacity to charge capacity during the first cycle, and can reflect the degree of metal ion consumption. It can be tested by any known method.
[0081] In this article, the DC impedance after 100 cycles is mainly used to characterize the internal resistance of the battery after 100 cycles, which can reflect the electronic conductivity of the battery and can be tested by any known method.
[0082] In this article, the capacity retention rate after 100 cycles is mainly used to characterize the cycle performance of the battery and can reflect the cycle performance of the battery, which can be tested by any known method.
[0083] In some embodiments, the carbon nanomaterial in the undercoat layer comprises a zero-dimensional carbon material and a one-dimensional carbon material.
[0084] In some embodiments, the carbon nanomaterial in the undercoat layer comprises only zero-dimensional carbon materials and one-dimensional carbon materials.
[0085] It is generally believed in the existing technology that compared with two-dimensional carbon materials, point-shaped zero-dimensional carbon materials and linear one-dimensional carbon materials require higher thickness or higher surface density to achieve uniform coverage of the current collector surface to achieve uniform deposition of metal ions in the electrolyte.
[0086] Although the mechanism is still unclear, the applicant unexpectedly discovered that, contrary to the general understanding in the prior art, the primer layer containing only zero-dimensional carbon materials and one-dimensional carbon materials can further reduce the nucleation overpotential of metal ions while reducing the surface density of the primer layer, helping to induce uniform deposition of metal ions on the current collector, and significantly improving the capacity retention rate of the battery after 100 cycles.
[0087] In some embodiments, the median particle size Dv50 of the zero-dimensional carbon material is 10 nm to 60 nm. In some embodiments, the median particle size Dv50 of the zero-dimensional carbon material can be 1 nm, 3 nm, 5 nm, 7 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm or 60 nm.
[0088] In this article, the term "median particle size" refers to the particle size corresponding to the cumulative particle size distribution percentage of the sample reaching 50%. Its physical meaning is that particles with a particle size larger than this account for 50%, and particles with a particle size smaller than this also account for 50%.
[0089] Controlling the median particle size Dv50 of zero-dimensional carbon materials to 10nm~60nm can further improve the uniformity of the carbon nanomaterial arrangement, greatly reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0090] In some embodiments, the aspect ratio of the one-dimensional carbon material is 500 to 50,000, optionally 1,000 to 10,000. In some embodiments, the aspect ratio of the one-dimensional carbon material can be 500, 600, 700, 800, 900, 1,000, 2,000, 3,000, 4,000, 5,000, 6,000, 7,000, 8,000, 9,000, 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, or 50,000.
[0091] As used herein, the term "aspect ratio" refers to the ratio of the length dimension of a one-dimensional carbon material to the tube diameter dimension.
[0092] Controlling the aspect ratio of the one-dimensional carbon material to 500-50,000 effectively reduces the nucleation overpotential of metal ions, inhibits dendrite growth, reduces the DC impedance of the battery after 100 cycles, and improves the battery's coulombic efficiency and capacity retention after 100 cycles. Controlling the aspect ratio of the one-dimensional carbon material to 1,000-10,000 can further improve the capacity retention after 100 cycles.
[0093] In some embodiments, the diameter of the one-dimensional carbon material is 1 nm to 20 nm, optionally 5 nm to 20 nm, and the length is 10 μm to 50 μm, optionally 20 μm to 30 μm. In some embodiments, the diameter of the one-dimensional carbon material can be 1 nm, 2 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm or 20 nm. In some embodiments, the length of the one-dimensional carbon material can be 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, 33 μm, 35 μm, 37 μm, 40 μm, 42 μm, 45 μm, 48 μm or 50 μm.
[0094] Controlling the tube diameter of the one-dimensional carbon material to 1nm-20nm and the length to 10μm-50μm can improve the uniformity of the carbon nanomaterial arrangement, effectively reduce the nucleation overpotential of metal ions, inhibit the growth of dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the battery's coulombic efficiency and capacity retention after 100 cycles. Controlling the tube diameter of the one-dimensional carbon material to 5nm-20nm can further leverage the advantages of the one-dimensional carbon material, further reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the battery's coulombic efficiency and capacity retention after 100 cycles. Controlling the length of the one-dimensional carbon material to 20μm-30μm can further reduce the DC impedance of the battery after 100 cycles.
[0095] In some embodiments, the median particle size Dv50 of the two-dimensional carbon material is no greater than 500 nm. In some embodiments, the median particle size Dv50 of the two-dimensional carbon material can be 1 nm, 3 nm, 5 nm, 7 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, or 500 nm.
[0096] Controlling the median particle size Dv50 of the two-dimensional carbon material to no more than 500nm can effectively reduce the nucleation overpotential of metal ions, inhibit the growth of dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0097] In some embodiments, the mass ratio of the two-dimensional carbon material, the one-dimensional carbon material, and the zero-dimensional carbon material is (0-10):(0-9):(0-9.5), wherein the masses of at least two of the two-dimensional carbon material, the one-dimensional carbon material, and the zero-dimensional carbon material cannot be 0 at the same time. In some embodiments, the mass ratio of the two-dimensional carbon material, the one-dimensional carbon material, and the zero-dimensional carbon material can be 8:0:2, 8:2:0, 0:2:8, 1:2:8, 2:2:8, 3:2:8, 5:2:8, 7:2:8, 9:2:8, 10:2:8, 3:9:8, 3:2:9.5, or 10:9:9.5.
[0098] Controlling the mass ratio of two-dimensional carbon materials, one-dimensional carbon materials, and zero-dimensional carbon materials within an appropriate range is beneficial to reducing the overpotential of metal ion deposition, inhibiting the dendritic behavior of metal ions, reducing the DC impedance of the battery after 100 cycles, and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0099] In some embodiments, the mass ratio of the one-dimensional carbon material to the zero-dimensional carbon material is (2:8) to (7:3). In some embodiments, the mass ratio of the one-dimensional carbon material to the zero-dimensional carbon material can be 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 4.5:5.5, 5:5, 5.5:4.5, 6:4, 6.5:3.5 or 7:3.
[0100] Controlling the mass ratio of one-dimensional carbon material and zero-dimensional carbon material within an appropriate range can greatly reduce the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0101] In some embodiments, the zero-dimensional carbon material comprises at least one selected from conductive carbon black, carbon nanodots, and fullerenes, and the conductive carbon black comprises at least one selected from Super P, Ketjen black, and acetylene black.
[0102] In some embodiments, the one-dimensional carbon material comprises at least one selected from carbon nanotubes, carbon nanohorns, carbon nanofibers, and carbon nanorods, and the carbon nanotubes comprise at least one selected from single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0103] In some embodiments, the two-dimensional carbon material comprises at least one selected from graphene and graphyne.
[0104] In this article, the term "single-walled carbon nanotube" refers to a seamless hollow cylinder formed by rolling up a single layer of graphene, with a tube diameter less than 100 nm and a tube length greater than 100 nm.
[0105] In this article, the term "multi-walled carbon nanotube" refers to a plurality of single-walled carbon nanotubes arranged concentrically, with a tube diameter of less than 100 nm and a tube length of more than 100 nm.
[0106] As used herein, the term "single-layer graphene" refers to a single-layer sheet structure composed of carbon atoms densely arranged in a periodic hexagonal honeycomb structure. For example, the thickness of a single-layer graphene is only 0.3 nm to 0.4 nm.
[0107] In some embodiments, the zero-dimensional carbon material comprises Ketjen black. In some embodiments, the zero-dimensional carbon material comprises Super P. In some embodiments, the zero-dimensional carbon material comprises Super P and fullerene. In some embodiments, the zero-dimensional carbon material comprises Super P and Ketjen black. In some embodiments, the zero-dimensional carbon material comprises carbon nanodots, Ketjen black, and acetylene black.
[0108] In some embodiments, the one-dimensional carbon material comprises single-walled carbon nanotubes. In some embodiments, the one-dimensional carbon material comprises multi-walled carbon nanotubes. In some embodiments, the one-dimensional carbon material comprises single-walled carbon nanotubes and carbon nanofibers. In some embodiments, the one-dimensional carbon material comprises single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0109] In some embodiments, the one-dimensional carbon material may also include oligo-walled carbon nanotubes.
[0110] In some embodiments, the graphene comprises one of single-layer graphene and multi-layer graphene.
[0111] As used herein, the term "oligo-walled carbon nanotubes" refers to a mixture comprising single-walled carbon nanotubes, double-walled carbon nanotubes, and triple-walled carbon nanotubes.
[0112] In this article, the term "multilayer graphene" refers to a stack of 2 to 10 single-layer graphene layers with a total thickness of less than 100 nm.
[0113] The aforementioned zero-dimensional, one-dimensional, and two-dimensional carbon materials possess excellent electrical conductivity, enabling the undercoat layer to serve as a conductive network for rapid electron transport. Furthermore, their nanoscale structure and arrangement also contribute to reducing current density, thereby lowering the overpotential for metal ion deposition, promoting uniform deposition of metal ions, and inhibiting dendritic behavior of metal ions. Furthermore, the aforementioned zero-dimensional, one-dimensional, and two-dimensional carbon materials also contribute to reducing the DC impedance of the battery after 100 cycles, improving the battery's coulombic efficiency, and increasing its capacity retention after 100 cycles.
[0114] In some embodiments, the one-dimensional carbon material in the primer layer is single-walled carbon nanotubes, and the zero-dimensional carbon material in the primer layer is conductive carbon black. In some embodiments, the zero-dimensional carbon material in the primer layer may be Super P, the zero-dimensional carbon material in the primer layer may be Ketjen black, or the zero-dimensional carbon material in the primer layer may be Super P, Ketjen black, and acetylene black.
[0115] The combination of single-walled carbon nanotubes and conductive carbon black can further reduce the overpotential of metal ion deposition, thereby reducing the DC impedance of the battery after 100 cycles, and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0116] In some embodiments, the thickness of the primer layer is 0.5 μm to 15 μm, and can be 1 μm to 8 μm. In some embodiments, the thickness of the primer layer can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.
[0117] The thickness of the primer layer on the surface of the negative electrode current collector is relatively small and cannot play the role of negative electrode active material, that is, it is a negative electrode sheet without negative electrode active material. During the first charge, metal is deposited on the surface of the negative electrode current collector so that the deposited metal can adhere to the primer layer on the surface of the negative electrode current collector. Controlling the thickness of the primer layer to 0.5μm to 15μm can provide enough nucleation sites to facilitate the uniform deposition of metal ions, effectively reducing the nucleation overpotential of metal ions and the DC impedance of the battery after 100 cycles, improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles, and also avoiding the impact of the primer layer on energy density. Controlling the thickness of the primer layer to 1μm to 8μm can further reduce the nucleation overpotential of metal ions, taking into account both nucleation sites and energy density to a greater extent.
[0118] In some embodiments, the basecoat layer has an areal density of 0.5 mg / 1540.25 mm 2 ~50mg / 1540.25mm 2 , optional 1mg / 1540.25mm 2 ~25mg / 1540.25mm 2 In some embodiments, the surface density of the primer layer may be 0.5 mg / 1540.25 mm 2 、1mg / 1540.25mm 2 , 2mg / 1540.25mm 2 、5mg / 1540.25mm 2 、7mg / 1540.25mm 2 、10mg / 1540.25mm2 、15mg / 1540.25mm 2 、20mg / 1540.25mm 2 , 25mg / 1540.25mm 2 、30mg / 1540.25mm 2 、35mg / 1540.25mm 2 、40mg / 1540.25mm 2 、45mg / 1540.25mm 2 or 50mg / 1540.25mm 2 .
[0119] In this article, the term "areal density" refers to the area of 1540.25mm 2 The quality of the base coating.
[0120] Control the surface density of the primer layer to 0.5mg / 1540.25mm 2 ~50mg / 1540.25mm 2 , which is conducive to the uniform distribution of nucleation sites and promotes the uniform deposition of metal ions, while not affecting the transmission behavior of electrons. The surface density of the base coating is controlled to be 1mg / 1540.25mm 2 ~25mg / 1540.25mm 2 , further taking into account the uniform distribution of nucleation sites and the rapid transport of electrons.
[0121] In some embodiments, the primer layer further comprises a binder, and the mass ratio of the carbon nanomaterial to the binder in the primer layer is 1:(0.1-2), optionally 1:(0.1-1). In some embodiments, the mass ratio of the carbon nanomaterial to the binder in the primer layer can be 1:0.1, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:1, 1:1.2, 1:1.5, 1:1.8, or 1:2.
[0122] Controlling the mass ratio of carbon nanomaterials to binders in the primer layer within an appropriate range is beneficial to the uniform dispersion of carbon nanomaterials and the uniform distribution of nucleation sites in the primer layer, inducing uniform deposition of metal ions and improving cycle performance.
[0123] In some embodiments, the current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector, and a composite current collector.
[0124] In some embodiments, the metal foil can be copper foil, aluminum foil, stainless steel foil, iron foil, zinc foil, or titanium foil, and the metal foam current collector can be copper foam, aluminum foam, or zinc foam. The metal mesh current collector can be copper mesh or aluminum mesh. The composite current collector includes a polymer base film and metal foil formed on both sides of the polymer base film. The composite current collector can be a "sandwich" structure, with the polymer base film located in the middle and metal foil provided on both sides. The polymer base film can be selected from one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
[0125] The above-mentioned current collector has excellent tensile strength and ductility, which is beneficial to the stability and safety of the battery.
[0126] [Positive electrode]
[0127] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.
[0128] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.
[0129] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.
[0130] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c(CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0131] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.
[0132] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).
[0133] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.
[0134] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0135] [Electrolytes]
[0136] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0137] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0138] In some embodiments, the electrolyte salt may be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.
[0139] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether.
[0140] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0141] [Isolation film]
[0142] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0143] In some embodiments, the material of the separator can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0144] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0145] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0146] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0147] [Secondary battery]
[0148] A secondary battery includes a negative electrode sheet, wherein the negative electrode sheet includes a current collector in some embodiments.
[0149] The present application does not particularly limit the shape of the secondary battery; it can be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example. In some embodiments, the secondary battery includes at least one of a lithium battery, a sodium battery, a magnesium battery, a potassium battery, and a zinc battery.
[0150] In some embodiments, the secondary battery further includes a positive electrode sheet, a separator, and an electrolyte.
[0151] In some embodiments, the secondary battery is a negative electrode-less sodium battery.
[0152] Anode-free sodium batteries contain no negative electrode active material, only a negative electrode current collector. During initial charging, sodium ions at the cathode receive electrons, depositing sodium metal on the current collector surface to form a sodium metal phase. During discharge, the sodium metal converts to sodium ions and returns to the positive electrode, enabling cyclical charging and discharging. Compared to sodium-ion secondary batteries and sodium metal batteries, anode-free sodium batteries can achieve higher energy density because they are not limited by negative electrode materials.
[0153] In some embodiments, the nucleation overpotential of sodium ion deposition on the current collector is 10 mV to 26 mV. In some embodiments, the nucleation overpotential of sodium ion deposition on the current collector can be 10 mV, 12 mV, 14 mV, 15 mV, 16 mV, 18 mV, 20 mV, 22 mV, 24 mV, 25 mV or 26 mV.
[0154] The nucleation overpotential of sodium ion deposition on the current collector can be measured by any means known in the art. As an example, the battery is charged at 25°C at a constant current of 0.1C to 100 μA, and the most negative potential obtained during the charge is recorded as the overpotential.
[0155] The nucleation overpotential of sodium ion deposition on the current collector is 10mV~26mV, which is conducive to the uniform deposition of sodium ions on the current collector and inhibits the growth of sodium dendrites.
[0156] In some embodiments, the DC impedance of the secondary battery after 100 cycles is 3Ω to 6Ω. In some embodiments, the DC impedance of the secondary battery after 100 cycles can be 3Ω, 3.2Ω, 3.5Ω, 3.8Ω, 4Ω, 4.3Ω, 4.5Ω, 4.7Ω, 5Ω, 5.3Ω, 5.5Ω, 5.8Ω, or 6Ω.
[0157] The DC impedance of a secondary battery can be tested by any means known in the art. As an example, at 25°C, the prepared battery is charged to 3.7V at a constant current of 1C, then charged at a constant voltage of 3.7V until the current drops to 0.05C, and the voltage V1 is recorded. Then, it is discharged to 2.5V at a constant current of 1C, and the voltage V2 is recorded. Then, (V2-V1) / 1 / 3C is used to obtain the internal resistance DCR1 of the battery after the first cycle. Then, after 5 minutes (stabilization time), the above steps are repeated for the same battery, and the internal resistance DCRn of the battery after the nth cycle (n=1, 2, 3...100) is recorded at the same time. The 100 point values of DCR1, DCR2, DCR3...DCR100 are used as the vertical coordinates, and the corresponding number of cycles is used as the horizontal coordinates to obtain a curve graph of the battery discharge DCR and the number of cycles.
[0158] The DC impedance of the secondary battery after 100 cycles is 3Ω~6Ω, indicating that the secondary battery has good electron transmission efficiency, which is beneficial to the battery performance.
[0159] In some embodiments, referring to FIG3 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0160] [Battery Module]
[0161] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0162] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0163] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0164] [Battery Pack]
[0165] In some embodiments, the battery modules described above may be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0166] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0167] [Electrical devices]
[0168] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.
[0169] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0170] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0171] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0172] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0173] Example
[0174] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0175] 1. Preparation method
[0176] Example 1
[0177] 1) Preparation of current collector
[0178] The carbon material (the carbon material is single-walled carbon nanotubes + Ketjen black, the mass ratio of single-walled carbon nanotubes to Ketjen black is 2:8, the length of the single-walled carbon nanotubes is 30 μm, the tube diameter is 20 nm, the aspect ratio is 1500, and the median particle size of Ketjen black is 30 nm) and the sodium alginate binder are added to deionized water in a mass ratio of 1:0.4 and stirred and mixed evenly to obtain a carbon material slurry; then the carbon material slurry is coated on the surface of the copper foil and dried to form a primer layer with a thickness of 2 μm. Finally, the current collector is obtained by cold pressing and slitting.
[0179] 2) Preparation of positive electrode sheet
[0180] Na4Fe3(PO4)2P2O7 (NFPP) material, conductive agent carbon black, polyvinylidene fluoride binder and N-methylpyrrolidone (NMP) are stirred and mixed in a weight ratio of 8:1:1 to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.
[0181] 3) Isolation film
[0182] Polypropylene film is used as the isolation film.
[0183] 4) Preparation of electrolyte
[0184] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate (NaPF6) was dissolved in ethylene glycol dimethyl ether (DME) organic solvent and stirred evenly to obtain the electrolyte with a sodium salt concentration of 1 mol / L in Example 1.
[0185] 5) Preparation of batteries
[0186] The positive electrode sheet, separator, and current collector are stacked in order, with the separator positioned between the positive and negative current collectors to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell and placed in an aluminum shell. The cells are then baked at 80°C to remove water, and then electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium metal battery product of Example 1.
[0187] Examples 2 to 6
[0188] The preparation methods of the batteries of Examples 2 to 6 are similar to that of the battery of Example 1, except that the length and diameter of the single-walled carbon nanotubes are adjusted. The specific parameters are shown in Table 1.
[0189] Examples 7 to 10
[0190] The preparation methods of the batteries of Examples 7 to 10 are similar to those of the battery of Example 1, except that the median particle size Dv50 of Ketjen Black is adjusted. The specific parameters are shown in Table 1.
[0191] Examples 11 to 14
[0192] The preparation methods of the batteries of Examples 11 to 14 are similar to those of the battery of Example 1, except that the mass ratio of single-walled carbon nanotubes to Ketjen black is adjusted. The specific parameters are shown in Table 1.
[0193] Examples 15 to 18
[0194] The preparation methods of the batteries of Examples 15 to 18 are similar to those of Example 1, except that the mass ratio of the sum of the mass of single-walled carbon nanotubes and Ketjen black to the mass of the sodium alginate binder is adjusted. The specific parameters are shown in Table 1.
[0195] Examples 19 to 22
[0196] The preparation methods of the batteries of Examples 19 to 22 are similar to that of the battery of Example 1, except that the thickness of the primer layer is adjusted. The specific parameters are shown in Table 1.
[0197] Examples 23 to 29
[0198] The preparation methods of the batteries of Examples 23 to 29 are similar to those of the battery of Example 1, except that the components of the carbon materials are adjusted. The specific parameters are shown in Table 1.
[0199] Example 30
[0200] The battery of Example 30 is prepared in a similar manner to the battery of Example 1, except that the carbon material is adjusted to graphene + carbon nanofiber + Ketjen black, and the mass ratio of graphene, single-walled carbon nanotube, and Ketjen black is 3:2:8. The specific parameters are shown in Table 1.
[0201] Example 31
[0202] The preparation method of the battery of Example 31 is similar to that of the battery of Example 30, except that the carbon material is adjusted to graphene + single-walled carbon nanotubes + Ketjen black. The specific parameters are shown in Table 1.
[0203] Examples 32 to 34
[0204] The preparation methods of the batteries of Examples 32 to 34 are similar to those of the battery of Example 31, except that the mass ratios of graphene, single-walled carbon nanotubes, and Ketjen black are adjusted. The specific parameters are shown in Table 1.
[0205] Examples 35 to 38
[0206] The preparation methods of the batteries of Examples 35 to 38 are similar to those of the battery of Example 34, except that the median particle size Dv50 of the graphene is adjusted. The specific parameters are shown in Table 1.
[0207] Examples 39 to 42
[0208] The preparation methods of the batteries of Examples 39 to 42 are similar to those of the battery of Example 34, except that the thickness of the primer layer is adjusted. The specific parameters are shown in Table 1.
[0209] Example 43
[0210] The preparation method of the battery of Example 43 is similar to that of the battery of Example 34, except that the solvent of the electrolyte is adjusted to ethylene carbonate. The specific parameters are shown in Table 1.
[0211] Comparative Example 1
[0212] The battery of Comparative Example 1 was prepared in a similar manner to the battery of Example 1, except that the carbon material was adjusted to contain only Ketjen black. The specific parameters are shown in Table 1.
[0213] Comparative Examples 2 to 4
[0214] The batteries of Comparative Examples 2 to 4 were prepared similarly to the battery of Comparative Example 1, except that the carbon materials were adjusted to include only single-walled carbon nanotubes, only Super P, and only graphene, respectively. The specific parameters are shown in Table 1.
[0215] Comparative Example 5
[0216] The preparation method of the battery of Comparative Example 5 is similar to that of the battery of Comparative Example 1, except that the solvent of the electrolyte is adjusted to ethylene carbonate. The specific parameters are shown in Table 1.
[0217] Comparative Example 6
[0218] The preparation method of the battery of Comparative Example 6 is similar to that of the battery of Comparative Example 1, but the primer layer containing the carbon material is not prepared on the current collector copper foil. The specific parameters are shown in Table 1.
[0219] (Single-walled carbon nanotubes, multi-walled carbon nanotubes, oligo-walled carbon nanotubes, carbon nanofibers, Ketjen Black, Super P, fullerene, and graphene are all commercially available)
[0220] 2. Performance Testing
[0221] 1. Carbon material particle size test
[0222] 1) Zero-dimensional carbon material median particle size Dv50 particle size test
[0223] According to the particle size distribution laser diffraction method specified in GB / T 19077-2016, 0.1g–0.13g of the zero-dimensional carbon material sample to be tested was weighed into a 50mL beaker. 5g of anhydrous ethanol was added, and a stirring bar approximately 2.5mm in diameter was placed in the beaker. The sample was then sealed with plastic wrap. After ultrasonic treatment for 5 minutes, the sample was transferred to a magnetic stirrer and stirred at 500 rpm for at least 20 minutes. Two samples were collected from each batch for testing. Testing was performed using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.
[0224] 2) Dimensional testing of one-dimensional and two-dimensional carbon materials
[0225] According to the particle size distribution laser diffraction method specified in GB / T 19077-2016, 0.1g–0.13g of the one-dimensional or two-dimensional carbon material sample to be tested was weighed into a 50mL beaker. 5g of anhydrous ethanol was added, and a stirring bar approximately 2.5mm in diameter was placed in the beaker. The sample was then sealed with plastic wrap. After ultrasonic treatment for 5 minutes, the sample was transferred to a magnetic stirrer and stirred at 500 rpm for at least 20 minutes. Two samples from each batch were dropped onto a copper grid for testing. Measurements were performed using a Sigma 500 scanning electron microscope (Zeiss Instruments GmbH, Germany).
[0226] 2. Base coating performance test
[0227] 1) Surface density test
[0228] When conducting the surface density test, take a pole piece of the specified area at room temperature and use a punching machine to punch a circular hole on the pole piece. The area of the circular hole is 1540.25mm 2 Then use an electronic balance to weigh its mass m1 (unit mg), then use the same method to punch a blank current collector (blank foil), and use an electronic balance to weigh its mass m2 (unit mg), and finally use the formula (m1-m2) / 1540.25 to get the surface density (unit mg / 1540.25mm 2 ).
[0229] 3. Battery performance test
[0230] 1) Overpotential test
[0231] The overpotential test process is as follows: at 25°C, the battery is charged to 100 μA at a constant current of 0.1C, and the most negative potential obtained during the process is recorded as the overpotential.
[0232] 2) Coulomb efficiency test
[0233] The coulomb test process is as follows: at 25°C, the prepared battery is charged to 3.7V at a constant current of 1 / 3C, then charged at a constant voltage of 3.7V until the current drops to 0.05C to obtain the initial charge capacity (Cc1), and then discharged to 2.5V at a constant current of 1 / 3C to obtain the initial discharge capacity (Cd1). The battery coulomb efficiency is calculated according to the following formula:
[0234] Coulombic efficiency = first discharge capacity (Cd1) / first charge capacity (Cc1) × 100%.
[0235] 3) Battery cycle capacity retention test
[0236] The battery capacity retention rate test process is as follows: at 25°C, the prepared battery is charged to 3.7V at a constant current of 1C, then charged at a constant voltage of 3.7V until the current drops to 0.05C, and then discharged to 2.5V at 3C. The obtained capacity is recorded as the initial capacity (C0). Repeat the above steps for the same battery mentioned above, and record the discharge capacity (Cn) of the battery after the nth cycle at the same time. Then the battery capacity retention rate after each cycle is Pn=Cn / C0×100%. The 100 point values P1, P2...100 are used as the vertical coordinates, and the corresponding number of cycles is used as the horizontal coordinates to obtain a curve graph of the battery capacity retention rate and the number of cycles. During this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2,...the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to the embodiment or comparative example in Table 2 are the data measured after 100 cycles under the above test conditions, that is, the value of P100. The test process of the comparative example and other embodiments is the same as above.
[0237] 4) DC resistance (DCR) test
[0238] The DC resistance (DCR) test procedure is as follows: At 25°C, the prepared battery is charged at a constant current of 1C to 3.7V, then charged at a constant voltage of 3.7V until the current drops to 0.05C. The voltage V1 is recorded. The battery is then discharged at a constant current of 1C to 2.5V, and the voltage V2 is recorded. The internal resistance DCR1 of the battery after the first cycle is calculated as (V2-V1) / 1 / 3C. The battery is then left to stand for 5 minutes (stabilization time), and the above steps are repeated for the same battery. The internal resistance DCRn of the battery after the nth cycle (n=1, 2, 3, ... 100) is simultaneously recorded. The 100 points (DCR1, DCR2, DCR3, ... DCR100) are plotted as the vertical axis, and the corresponding cycle number is plotted as the horizontal axis to create a curve plotting the battery discharge DCR versus cycle number.
[0239] 5) Sodium dendrite test
[0240] After 100 cycles, the battery was disassembled in an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), and the surface morphology of the negative electrode was visually observed to determine whether sodium dendrites had formed. A negative electrode with no white spots was considered to have no sodium dendrites, a negative electrode with sporadic white spots was considered to have mild sodium dendrites, and a negative electrode with dense white spots was considered to have severe sodium dendrites. The test procedures for the comparative example and other examples were the same as above.
[0241] 3. Analysis of test results of various embodiments and comparative examples
[0242] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.
[0243] Table 1 Preparation parameters of Examples and Comparative Examples
[0244]
[0245]
[0246]
[0247] Table 2 Performance parameter test results of embodiments and comparative examples
[0248]
[0249]
[0250] Based on the above results, the undercoat layers of Examples 1-43 include carbon nanomaterials, wherein the carbon nanomaterials include at least two selected from zero-dimensional carbon materials, one-dimensional carbon materials, and two-dimensional carbon materials. The zero-dimensional carbon material is selected from one of Super P, Ketjen Black, and fullerene. The one-dimensional carbon material is selected from one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon nanofibers. The two-dimensional carbon material is graphene. A comparison of Examples 1-43 and Comparative Example 6 shows that the undercoat layer formed on the surface of the current collector copper foil facilitates the uniform distribution of nucleation sites, reduces the nucleation overpotential of sodium ions, and inhibits the growth of sodium dendrites. Furthermore, the undercoat layer comprising carbon nanomaterials also helps reduce the DC impedance of the battery after 100 cycles, improves the coulombic efficiency of the battery, and improves the capacity retention rate after 100 cycles. From the comparison of Examples 1 to 43 and Comparative Examples 1 to 5, it can be seen that compared with the base coating layer containing only one of zero-dimensional carbon material, one-dimensional carbon material, and two-dimensional carbon material, the base coating layer includes two or three of zero-dimensional carbon material, one-dimensional carbon material, and two-dimensional carbon material, which is more conducive to reducing the nucleation overpotential of sodium ions, inhibiting the growth of sodium dendrites, reducing the DC impedance of the battery after 100 cycles, and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0251] From the comparison of Examples 1 to 6 with Comparative Examples 1 to 6, it can be seen that controlling the aspect ratio of the single-walled carbon nanotubes to 500 to 50,000 can effectively reduce the nucleation overpotential of sodium ions, inhibit the growth of sodium dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency and capacity retention rate after 100 cycles. From the comparison of Examples 1, 3 to 5 with Examples 2 and 6, it can be seen that controlling the aspect ratio of the single-walled carbon nanotubes to 1000 to 10,000 can further improve the capacity retention rate after 100 cycles.
[0252] From the comparison of Examples 1 to 6 with Comparative Examples 1 to 6, it can be seen that controlling the diameter of the single-walled carbon nanotubes to be 1nm to 20nm and the length to be 10μm to 50μm can effectively reduce the nucleation overpotential of sodium ions, inhibit the growth of sodium dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison of Examples 1 and 3 with Examples 2 and 4, it can be seen that controlling the length of the single-walled carbon nanotubes to be 20μm to 30μm can further reduce the DC impedance of the battery after 100 cycles. From the comparison of Examples 4 to 5 with Example 6, it can be seen that controlling the diameter of the single-walled carbon nanotubes to be 5nm to 20nm can further reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison between Examples 1 and 3 and Examples 2, 4 to 6, it can be seen that controlling the diameter of the single-walled carbon nanotubes to 5 nm to 20 nm and the length to 20 μm to 30 μm can greatly reduce the DC impedance of the sodium battery after 100 cycles.
[0253] From the comparison of Examples 1, 8 to 9 with Examples 7 and 10, it can be seen that controlling the value particle size Dv50 of Ketjen black to 10 nm to 60 nm can greatly reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0254] From the comparison of Examples 1, 12 to 13 with Examples 11 and 14, it can be seen that controlling the mass ratio of single-walled carbon nanotubes to Ketjen black to (2:8) to (7:3) can greatly reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0255] From the comparison of Examples 1, 15 to 18 with Comparative Examples 1 to 6, it can be seen that controlling the mass ratio of carbon nanomaterial to binder to 1: (0.1 to 2) can effectively reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison of Examples 1, 15 to 17 with Example 18, it can be seen that controlling the mass ratio of carbon nanomaterial to binder to 1: (0.1 to 1) can further reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0256] Comparisons of Examples 19-22 with Comparative Examples 1-6, and Examples 39-42 with Comparative Examples 1-6, show that controlling the thickness of the single-walled carbon nanotube-Ketjen black undercoat layer to 0.5 μm to 15 μm can effectively reduce the sodium ion nucleation overpotential and the DC impedance of the battery after 100 cycles, while improving the battery's coulombic efficiency and capacity retention after 100 cycles. Comparisons of Examples 1, 20-21 with Examples 19 and 22, and Examples 31, 40-41 with Examples 39 and 42 show that controlling the thickness of the single-walled carbon nanotube-Ketjen black undercoat layer to 1 μm to 8 μm can further reduce the sodium ion nucleation overpotential.
[0257] From the comparison of Examples 1, 23 to 31 with Comparative Examples 1 to 6, it can be seen that compared with the single-walled carbon nanotube primer, Ketjen black primer, Super P primer or graphene primer, the single-walled carbon nanotube-Ketjen black primer, single-walled carbon nanotube-Super P primer, oligo-walled carbon nanotube-Ketjen black primer, multi-walled carbon nanotube-Ketjen black primer, single-walled carbon nanotube-fullerene primer, carbon nanofiber-Ketjen black primer, single-walled carbon nanotube-graphene primer, Ketjen black-graphene primer, carbon nanofiber-Ketjen black-graphene primer and single-walled carbon nanotube-Ketjen black-graphene primer have lower nucleation overpotentials of sodium ions, inhibit the growth of sodium dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0258] From the comparison of Examples 1 and 23 with Example 26, it can be seen that compared with the single-walled carbon nanotube-fullerene primer layer, the single-walled carbon nanotube-Ketjen black primer layer and the single-walled carbon nanotube-Super P primer layer have lower sodium ion nucleation overpotential, which greatly reduces the DC impedance of the battery after 100 cycles, and improves the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0259] From the comparison between Example 1 and Example 31, Example 19 and Example 39, Example 20 and Example 40, Example 21 and Example 41, and Example 22 and Example 42, it can be seen that compared with the single-walled carbon nanotube-Ketjen black-graphene base coating, the single-walled carbon nanotube-Ketjen black base coating has a lower surface density, a lower nucleation overpotential, and a higher capacity retention rate after 100 cycles.
[0260] From the comparison of Examples 1, 23 to 27 with Examples 28 to 29, it can be seen that compared with the graphene-single-walled carbon nanotube primer and the graphene-Ketjen black primer, the single-walled carbon nanotube-Ketjen black primer, the single-walled carbon nanotube-Super P primer, the oligo-walled carbon nanotube-Ketjen black primer, the multi-walled carbon nanotube-Ketjen black primer, the single-walled carbon nanotube-fullerene primer, and the carbon nanofiber-Ketjen black primer have lower surface density and sodium ion nucleation overpotential, and their batteries have lower DC impedance after 100 cycles, higher coulombic efficiency, and capacity retention after 100 cycles.
[0261] From the comparison of Examples 1, 11 to 14, 28 to 29, and 31 to 34 with Comparative Examples 1 to 6, it can be seen that controlling the mass ratio of graphene, single-walled carbon nanotubes, and Ketjen black to (0 to 10): (0 to 9): (0 to 9.5) can effectively reduce the nucleation overpotential of sodium ions, inhibit the growth of sodium dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0262] From the comparison of Examples 1, 35 to 38 and Comparative Examples 1 to 6, it can be seen that controlling the median particle size Dv50 of graphene to be no more than 500 nm can effectively reduce the nucleation overpotential of sodium ions, inhibit the growth of sodium dendrites, reduce the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0263] From the comparison between Example 1 and Example 43, it can be seen that compared with ethylene carbonate as the solvent of the electrolyte, ethylene glycol dimethyl ether as the solvent of the electrolyte can effectively reduce the nucleation overpotential of sodium ions and the DC impedance of the battery after 100 cycles, and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0264] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A current collector having a primer layer formed on its surface, characterized in that: The undercoat layer includes a carbon nanomaterial, and the carbon nanomaterial includes at least two selected from a zero-dimensional carbon material, a one-dimensional carbon material, and a two-dimensional carbon material.
2. The current collector according to claim 1, characterized in that The carbon nanomaterial in the undercoat layer includes a zero-dimensional carbon material and a one-dimensional carbon material.
3. The current collector according to claim 1 or 2, characterized in that: The median particle size Dv50 of the zero-dimensional carbon material is 10 nm to 60 nm.
4. The current collector according to any one of claims 1 to 3, characterized in that The aspect ratio of the one-dimensional carbon material is 500 to 50,000, and can be optionally 1,000 to 10,000.
5. The current collector according to any one of claims 1 to 4, characterized in that The tube diameter of the one-dimensional carbon material is 1 nm to 20 nm, and may be 5 nm to 20 nm, and the length is 10 μm to 50 μm, and may be 20 μm to 30 μm.
6. The current collector according to any one of claims 1 to 5, characterized in that The median particle size Dv50 of the two-dimensional carbon material is not greater than 500 nm.
7. The current collector according to any one of claims 1 to 6, characterized in that The mass ratio of the two-dimensional carbon material, the one-dimensional carbon material, and the zero-dimensional carbon material is (0-10):(0-9):(0-9.5), wherein the masses of at least two of the two-dimensional material, the one-dimensional carbon material, and the zero-dimensional carbon material cannot be 0 at the same time.
8. The current collector according to any one of claims 1 to 7, characterized in that The mass ratio of the one-dimensional carbon material to the zero-dimensional carbon material is (2:8) to (7:3).
9. The current collector according to any one of claims 1 to 8, characterized in that The zero-dimensional carbon material comprises at least one selected from conductive carbon black, carbon nanodots, and fullerenes, and the conductive carbon black comprises at least one selected from Super P, Ketjen black, and acetylene black.
10. The current collector according to any one of claims 1 to 9, characterized in that The one-dimensional carbon material comprises at least one selected from carbon nanotubes, carbon nanohorns, carbon nanofibers, and carbon nanorods, and the carbon nanotubes comprise at least one selected from single-walled carbon nanotubes and multi-walled carbon nanotubes.
11. The current collector according to any one of claims 1 to 10, characterized in that The two-dimensional carbon material comprises at least one selected from graphene and graphyne.
12. The current collector according to any one of claims 1 to 11, characterized in that The one-dimensional carbon material in the primer layer is single-walled carbon nanotubes, and the zero-dimensional carbon material in the primer layer is conductive carbon black.
13. The current collector according to any one of claims 1 to 12, characterized in that The thickness of the primer layer is 0.5 μm to 15 μm, and can be optionally 1 μm to 8 μm.
14. The current collector according to any one of claims 1 to 13, characterized in that The surface density of the primer layer is 0.5 mg / 1540.25 mm 2 ~50mg / 1540.25mm 2 , optional 1mg / 1540.25mm 2 ~25mg / 1540.25mm 2 .
15. The current collector according to any one of claims 1 to 14, characterized in that The primer layer further comprises a binder, and the mass ratio of the carbon nanomaterial to the binder in the primer layer is 1:(0.1-2), and can be optionally 1:(0.1-1).
16. The current collector according to any one of claims 1 to 15, characterized in that The current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector.
17. Use of the current collector according to any one of claims 1 to 16 in a sodium battery.
18. A secondary battery, characterized in that: The invention comprises a negative electrode sheet, wherein the negative electrode sheet comprises the current collector according to any one of claims 1 to 16.
19. The secondary battery according to claim 18, wherein The secondary battery includes at least one of a lithium battery, a sodium battery, a magnesium battery, a potassium battery, and a zinc battery.
20. The secondary battery according to claim 18 or 19, characterized in that: The secondary battery is a negative electrode-free sodium battery.
21. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 18 to 20.
22. A battery pack, characterized in that: The invention comprises a secondary battery selected from any one of claims 18 to 20 or a battery module according to claim 21.
23. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery according to any one of claims 18 to 20, the battery module according to claim 21, and the battery pack according to claim 22.
Citation Information
Cited By
Negative-electrode-free secondary battery, modified graphite, modified current collector and preparation method thereof
CN119528135A
Negative electrode-free secondary battery, modified graphite, modified current collector and preparation method thereof
CN119528135B
Negative plate, battery and electric device
CN121123183A
Modified negative electrode current collector, preparation method and application thereof, and negative-electrode-free sodium metal battery
CN121964666A
